Functional Role of P-Glycoprotein and Binding Protein Effect on the Placental Transfer of Lopinavir/Ritonavir in the Ex Vivo Human Perfusion Model - Pierre-Francois Ceccaldi; Laurent Gavard; Laurent Mandelbrot; Elisabeth Rey; Robert Farinotti; Jean-Marc Treluyer; Sophie Gil (Obstetrics and Gynecology International)
Aims. To study the influence of P-glycoprotein (P-glycoprotein, ABCB1, MDR1) function on placental transfer of lopinavir with ritonavir at different albumin concentrations. Methods. Cotyledons were perfused with lopinavir, ritonavir, and the internal control antipyrin, at various albumin concentrations (10, 30, 40 g/L). After the control phase of each experiment, the P-glycoprotein inhibitor ciclosporin A was added at middle perfusion (45 minutes). Fetal Transfer Rate (FTR) and Clearance Index (CLI) were compared between the 2 phases. Results. In the control phase, the clearance index of lopinavir decreased from 0.401 ± 0.058 to 0.007 ± 0.027, as albumin concentrations increased from 10 g/L to higher concentrations (30, 40 g/L). When adding ciclosporin A at physiological albumin concentrations, the clearance index of lopinavir increased significantly 10.3 fold (95% of CI difference [−0.156, −0.002], P=.046) and became positive for ritonavir. Conclusions. Even at high albumin concentrations, inhibition of placental P-glycoprotein increased placental transfer of lopinavir, suggesting that this efflux pump actively reduces placental transfer of the drug. This mechanism may play a role in fetal exposure to maternal antiretroviral therapy.